2024
DOI: 10.1186/s12916-024-03363-6
|View full text |Cite|
|
Sign up to set email alerts
|

Olfactory bulb anomalies in KBG syndrome mouse model and patients

Kara Goodkey,
Anita Wischmeijer,
Laurence Perrin
et al.

Abstract: ANKRD11 (ankyrin repeat domain 11) is a chromatin regulator and the only gene associated with KBG syndrome, a rare neurodevelopmental disorder. We have previously shown that Ankrd11 regulates murine embryonic cortical neurogenesis. Here, we show a novel olfactory bulb phenotype in a KBG syndrome mouse model and two diagnosed patients. Conditional knockout of Ankrd11 in murine embryonic neural stem cells leads to aberrant postnatal olfactory bulb development and reduced size due to reduction of the olfactory bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
1
1
0
Order By: Relevance
“…We and others have also shown that Yoda mice or mice with Ankrd11 knockdown in cortical progenitors and their derivatives have impaired neurogenesis and neuron positioning, which may suggest altered neuronal migration 13 , 76 . This was recently corroborated in our study, which showed that Ankrd11 knockout in neural stem cells leads to severe neuroblast migration defect in the rostral migratory stream 75 . Together, the results presented in this study and previous reports suggest that Ankrd11 may have unique roles in each cell type it is expressed in and that Ankrd11’s function may depend on cellular identity and environment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We and others have also shown that Yoda mice or mice with Ankrd11 knockdown in cortical progenitors and their derivatives have impaired neurogenesis and neuron positioning, which may suggest altered neuronal migration 13 , 76 . This was recently corroborated in our study, which showed that Ankrd11 knockout in neural stem cells leads to severe neuroblast migration defect in the rostral migratory stream 75 . Together, the results presented in this study and previous reports suggest that Ankrd11 may have unique roles in each cell type it is expressed in and that Ankrd11’s function may depend on cellular identity and environment.…”
Section: Discussionsupporting
confidence: 85%
“…However, we also showed a decrease in cell proliferation in some, but not all, craniofacial regions, with no difference in apoptosis 28 . Moreover, our work with Yoda mice, which carry a heterozygous splice site-like mutation in Ankrd11 , or with mice that have Ankrd11 knocked down or out in neural stem cells, shows that Ankrd11 regulates embryonic neural stem cell proliferation 13 , 75 . We and others have also shown that Yoda mice or mice with Ankrd11 knockdown in cortical progenitors and their derivatives have impaired neurogenesis and neuron positioning, which may suggest altered neuronal migration 13 , 76 .…”
Section: Discussionmentioning
confidence: 87%